Interacciones de genotipos por sistema de cultivo en frijol y maiz - Davis, J.H.C. (International Center for Tropical Agriculture, 1979)
The results are presented of 3 expt conducted at CIAT to improve var. destined for use in multiple-cropping systems; (1) evaluation of bean var. (bush and climbing) in 2 cropping systems, monoculture and in association with maize; (2) evaluation of 20 maize genotypes in monoculture and in association with 2 bean types (habits II and IV); and (3) evaluation of 3 maize and 10 climbing bean genotypes. It is concluded that there are certain genotypic combinations of maize and beans that are better but that are not necessarily the best for monoculture. Nevertheless, evidence indicates that when certain simple plant characteristics are taken into account for both maize and beans, better combinations can be predicted. (CIAT)